Echuca : a centenary history - Priestley, Susan, 1938-; Echuca (Vic. : Borough). Council (Brisbane : Jacaranda, 1965)
Brief references to natives and early contacts, quotes E.M. Curr in description & general life.
Published in association with Borough Council of Echuca.
Includes bibliographical references and index.
Keywords: Bangerang people (S40) (Vic SJ55-02); Bangerang / Kwat Kwat / Waveroo people (S40) (Vic SJ55-02); Daily life; Settlement and contacts - Colonisation; Echuca (Vic.) -- History; Echuca (N Vic SJ55-01)